To stop a warlord my story of justice, grace, and the fight for peace - Davis, Shannon Sedgwick (New York Spiegel & Grau, 2019)
Human rights lawyer Shannon Sedgwick Davis runs the Bridgeway Foundation, whose stated mission is to end mass atrocities around the world. When she spoke to survivors of warlord Joseph Kony's brutal attacks across Central Africa, she knew she would fight to ensure every mother there had the right that she had, to sing their children to sleep at night and trust that they will be safe til morning. When nations had failed to shield families in danger, she'd come to hire a private army to protect them. Millions had been affected by the violence of the Lord's Resistance Army, led by Kony, including tens of thousands of children who had been abducted from their homes, swept into the jungles and forced to become child soldiers, never to be seen again. Guided by her faith and driven by her moral responsibility as an activist, Davis pushed tirelessly for intervention, using every contact she had in Washington, to the highest levels of the State Department--but since it wouldn't serve our national interests, the issue languished. Davis's efforts to report on the conflict and help survivors were valuable--but they were putting band-aids on bulletholes. Davis realized that to truly stand by Bridgeway's mission, they would have to become the ones they were waiting for. Davis knew she had to act, but this was uncharted territory and she feared that hiring a private army to stop the LRA might lead to more chaos. The decision weighed heavily on her heart, but when she spoke to her mentor Archbishop Desmond Tutu, he took her hand, and told her to put her fears to rest
Keywords: Davis, Shannon Sedgwick